Strategic Development of Business Models: A Case study of the PT. Timah Agro Manunggal in Indonesia - Haq, Husnul (Archives of Business Research, 2019)
Business Model Canvas manages to make business model simple, and easily understood while capturing the complexities of how enterprises function. The research purpose is to evaluate the business model on a new company used Business Model Canvas (BMC). BMC consists of customer segments, value propositions, channels, customer relationship, revenue streams, key resources, key activities, key partnership, and cost structure. The research method was used qualitative descriptive analysis. The data collected using in-depth interviews and observations. The data analysis using reduction, data display, and conclusion techniques. Analysis SWOT is to evaluate the business model on a PT. Timah Agro Manunggal as agribusiness company. The results show that the nine blocks of the business model canvas can be the initial identification to form a business development strategy. The conclusion of this paper is the business development strategy at PT. Timah Agro Manunggal can be creating a competitive advantage through marketing strategies, collaboration strategies, optimizing partnership relationships with stakeholders. The business model canvas is an effective tool for maximizing the planning of the development of the business model of agribusiness companies for the long term.